Caribbean food cultures : culinary practices and consumption in the Caribbean and its diasporas - Beushausen, Wiebke; Brüske, Anne; Commichau, Ana-Sofia; Helber, Patrick; Kloss, Sinah (Postcolonial studies, 2014)
"Caribbean Food Cultures" approaches the matter of food from the perspectives of anthropology, sociology, cultural and literary studies. Its strong interdisciplinary focus provides new insights into symbolic and material food practices beyond eating, drinking, cooking, or etiquette. The contributors discuss culinary aesthetics and neo/colonial gazes on the Caribbean in literary documents, audiovisual media, and popular images. They investigate the negotiation of communities and identities through the preparation, consumption, and commodification of "authentic" food. Furthermore, the authors emphasize the influence of underlying socioeconomic power relations for the reinvention of Caribbean and Western identities in the wake of migration and transnationalism. The anthology features contributions by renowned scholars such as Rita De Maeseneer and Fabio Parasecoli who read Hispano-Caribbean literatures and popular culture through the lens of food studies.